Framing Honor Killing in Turkey as a Kurdish Problem: A Postcolonial Analysis - Mufti Rasyid; Yulia Nasrul Latifi; Ibnu Burdah; Muhammad Khoirul Malik (Universitas prof. Dr. Moestopo (Beragama), 2026)
Honor killing refers to the murder of a family member (usually female) who have brought shame or dishonor upon the family. This article explores how honor killing is discussed in Turkey, with particular attention to how the practice is frequently linked to the Kurdish ethnic minority. Drawing on Robert Entman’s framing theory and supported by postcolonial critique, the study analyzes twelve news reports published between 2016 and 2023 in three major Turkish outlets. The analysis indicates that Turkish media and state discourse (manifested in legal system) repeatedly frame honor killing in ways that marginalize and stigmatize Kurds. By attaching the practice to Kurdish identity, these discourses normalize an image of Kurds as ‘backward’ and Turks as modern, reproducing orientalist binaries of tradition versus civilization. Building on Spivak’s concept of the subaltern, the article argues that Kurdish women who always become the victims of honor killing are rendered voiceless and are instrumentalized as symbolic evidence of Kurdish ‘backwardness’. In this framing, women’s suffering becomes a rhetorical device that helps justify state authority and domination over particular minorities.